Analysis of Mitochondrial DNA from a Burned, Ninhydrin‐Treated Paper Towel1. Issue 3 (25th February 2016) - Buś, Magdalena M.; Nilsson, Martina; Allen, Marie
Abstract: Contact‐based evidence is likely to have limited quantities of DNA and may yield mixed profiles due to preexisting or contaminating DNA. In a recent arson investigation, a paper towel was collected and used as circumstantial evidence. The paper towel was partially burned and was likely set on fire with flammable liquid. As part of the investigation, the paper towel was treated with ninhydrin to visualize fingerprint evidence. Initial DNA analysis of two swabs was negative for short tandem repeat (STR) markers and revealed a mixture of mitochondrial DNA (mtDNA). Analysis of 13 additional cuttings yielded four more mixed profiles, but also two samples with a common single‐source profile. The single‐source mtDNA profile matched that of the primary suspect in the case. Thus, even if initial mtDNA analysis yields a mixed profile, a sampling strategy involving multiple locations can improve the chance of obtaining valuable single‐source mtDNA profiles from compromised evidence in criminal casework.